ChemInform Abstract: Th3 [Th6(OH)4O4(H2O)6] (SO4)12(H2O)13: A Self‐Assembled Microporous Open‐Framework Thorium Sulfate. Issue 51 (5th December 2016) - Lin, Jian; Jin, Geng Bang; Soderholm, L.
Abstract: Microcrystals of Th3 [Th6 (OH)4 O4 (H2 O)6 ] (SO4 )12 (H2 O)13 ·xTh 4+ ·ySO4 2‐ ·nH2 O (I) are isolated by evaporation of an aqueous solution of Th(OH)4 in H2 SO4 (pH 2.4—2.5, 3 d).